Determinants of firm’s efficiency: evidence from firms in financial distress / Nur Syahirah Zulkifli - Zulkifli, Nur Syahirah (2022)
In this paper, we analyze a panel data of 85 financially distressed firms to determine firm’s efficiency and variables that important in explaining the level of efficiency of financial distress firms in Malaysia. Panel data analysis technique is used to determine the optimal model to explain the level of efficiency in financial distress firm. In addition, this paper finds evidence suggesting the relevance of profitability and size which implies the importance of these factors in determining the level of efficiency in financial distress firm. Other variables such as leverage and tangible asset have no significant impact on the status of firms in financial distress. This paper used fixed effect (FE) model to analyze the variables, the result is positively significant relationship on two variables that have been chosen, these variables are profitability and size.